Electrical installations in hazardous areas - McMillan, Alan (Butterworth-Heinemann, 1998)
The Health and Safety at Work Act, together with current and impending EU Directives, obliges those responsible for hazardous areas, those who work in such areas and those who supply equipment for use in such areas to demonstrate that they have taken all necessary and reasonable steps to prevent fires and explosions. This book addresses these issues, seeks to explain the ever increasing complexity of standards and codes pertaining to this field and describes their method of application and the application of other procedures to assist those involved. The only book which provides comprehensive cover of this vital area. Written by a leading Internationally recognised UK authority in this field.